Breathing Exercise for Chronic Obstructive Pulmonary Disease Patient: Scoping Review - Umifa, Kaslinda Nur; Jenie, Ikhlas Muhammad (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Chronic Obstructive pulmnonary disease is a respiratory disorder that cause several symptoms as dyspnea, chronic cough and fatigue. These symptoms can be overcome by doing breathing exercise. This scoping review to determine the benefits and types of breathing exercises in COPD patient. The databases used in the scoping revieware PubMed, Science Direct, ClincalKey for Nursing. The inclusion criteria were English articles, COPD patients. The final results obtained 7 articles that meet the criteria in scoping review. The analysis shows that yoga breathing exercise. Pursed-lips breathing, inspiratory and expiratory muscle training which can increase oxygen saturation, mucus production, vital lung capacity, the value of six minute walk tests, reduce dyspnea and frequency exhalation. The conclusion of the review of the seven articles that the Breathing exercise consist of several types of exercises that can reduce symptoms or problems experienced in COPD patient. Penyakit Paru Obstruktif Kronik adalah gangguan yang menyebabkan beberapa gejala seperti sesak napas, batuk kronis dan kelelahan. Gejala tersebut dapat diatasi dengan melakukan latihan pernapasan. Scoping review ini untuk mengetahui manfaat dan jenis latihan pernapasan pada pasien PPOK. Data dasar yang digunakan dalam pelingkupan adalah PubMed, Science Direct, ClincalKey untuk Keperawatan. Kriteria inklusi adalah artikel berbahasa Inggris, pasien PPOK. Hasil akhir diperoleh 7 artikel yang memenuhi kriteria dalam mengikuti pelingkupan. Analisis menunjukkan bahwa yoga adalah latihan pernapasan.Latihan pernapasan bibir, inspirasi dan ekspirasi yang dapat meningkatkan saturasi oksigen, produksi lendir, kapasitas vital paru-paru, nilai tes jalan enam menit, mengurangi dispnea dan frekuensi pernafasan.